Genomics, genetics and breeding of tropical legumes for better livelihoods of smallholder farmers. (17th April 2018) - Ojiewo, Chris; Monyo, Emmanuel; Desmae, Haile; Boukar, Ousmane; Mukankusi‐Mugisha, Clare; Thudi, Mahendar; Pandey, Manish K.; Saxena, Rachit K.; Gaur, Pooran M.; Chaturvedi, Sushil K.; Fikre, Asnake; Ganga Rao, NPVR; et al.
Abstract: Legumes are important components of sustainable agricultural production, food, nutrition and income systems of developing countries. In spite of their importance, legume crop production is challenged by a number of biotic (diseases and pests) and abiotic stresses (heat, frost, drought and salinity), edaphic factors (associated with soil nutrient deficits) and policy issues (where less emphasis is put on legumes compared to priority starchy staples). Significant research and development work have been done in the past decade on important grain legumes through collaborative bilateral and multilateral projects as well as the CGIAR Research Program on Grain Legumes (CRP‐GL). Through these initiatives, genomic resources and genomic tools such as draft genome sequence, resequencing data, large‐scale genomewide markers, dense genetic maps, quantitative trait loci (QTLs) and diagnostic markers have been developed for further use in multiple genetic and breeding applications. Also, these mega‐initiatives facilitated release of a number of new varieties and also dissemination of on‐the‐shelf varieties to the farmers. More efforts are needed to enhance genetic gains by reducing the time required in cultivar development through integration of genomics‐assisted breeding approaches and rapid generation advancement.